ICE. - Snoonian, Deborah (Architectural Record, 2005)
This article focuses on a Java-based program introduced by Dirtt Environmental Solutions. Despite the rather unfortunate name of the company that makes it, ICE helps interior designers chill out about arranging modular workspaces. This Java-based program, which can be used on its own or as a plug-in to Autodesk or Bentley products, enables designers to explore and compare different layout concepts using a library of interior components from manufacturers who subscribe to ICE's service.